1996
DOI: 10.1007/bf00053792
|View full text |Cite
|
Sign up to set email alerts
|

Accuracy of ozonesonde measurements in the troposphere

Abstract: Measurements of atmospheric ozone at concentrations typical of the free troposphere have been compared for ECC sondes and a UV-absorption photometer, using a Bendix chemiluminescent analyser as a transfer standard. Comparisons were conducted in the laboratory and in the tropospheric part of the atmosphere. It was found that the measurements agreed to within 4% provided that the background current for the ECC sonde was measured before exposure to ozone in the preparation procedure, and was assumed to be constan… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
29
0

Year Published

1998
1998
2018
2018

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 42 publications
(30 citation statements)
references
References 5 publications
1
29
0
Order By: Relevance
“…Common, although not universally accepted, is the cell current reading 10 min after the ozone conditioning. Some research groups use a cell current reading just before the high ozone conditioning as suggested by Reid et al (1996) or a cell current reading shortly before launch.…”
Section: The Ecc Backgroundmentioning
confidence: 99%
See 2 more Smart Citations
“…Common, although not universally accepted, is the cell current reading 10 min after the ozone conditioning. Some research groups use a cell current reading just before the high ozone conditioning as suggested by Reid et al (1996) or a cell current reading shortly before launch.…”
Section: The Ecc Backgroundmentioning
confidence: 99%
“…Thus, some questions remain, whether the results shown here are also applicable to this ozone sonde type and to the CEPEX measurements. Reid et al (1996) used model 5A ozone sondes and the 1% full buffer solution in a comparison with a reference ozone analyzer. Their measurements document background measurements prior to cell conditioning (I bg1 = 0.05 µA), after ozone conditioning (I * bg2 = 0.1 µA), and before launch (I * bg2 = 0.01 µA).…”
Section: Ozone Observations During Cepexmentioning
confidence: 99%
See 1 more Smart Citation
“…Following the recommendation of Reid et al (1996), a constant background current correction was applied to ozonesonde measurements throughout the troposphere, in preference to the standard pressure-varying correction. Ozonesonde profiles treated in this way were consistent with those from the Geophysica aircraft on corresponding flight days, within ∼5 ppbv (profiles not shown).…”
Section: Ozonesonde Instrumentationmentioning
confidence: 99%
“…The term i b represents the blank current in an ECC, and is generally measured when an ECC is exposed to ozone-free air for a period of around 10 minutes. Many researchers have investigated the interference of a background current on the accuracy of an ECC ozonesonde (Thornton and Niazy, 1982;Barnes et al, 1985;Komhyr et al, 1995;Reid et al, 1996;Boyd et al, 1998;Smit et al, 2007;Vomel and Diaz, 2010). Pump sampling efficiencies can become important at low pressure environment (Johnson et al, 2002).…”
Section: Typical Data Processing Equationmentioning
confidence: 99%